What can megastudies tell us about the orthographic structure of English words?. Issue 8 (August 2015) - Chetail, Fabienne; Balota, David; Treiman, Rebecca; Content, Alain
Although the majority of research in visual word recognition has targeted single-syllable words, most words are polysyllabic. These words engender special challenges, one of which concerns their analysis into smaller units. According to a recent hypothesis, the organization of letters into groups of successive consonants (C) and vowels (V) constrains the orthographic structure of printed words. So far, evidence has been reported only in French with factorial studies of relatively small sets of items. In the present study, we performed regression analyses on corpora of megastudies (English and British Lexicon Project databases) to examine the influence of the CV pattern in English. We compared hiatus words, which present a mismatch between the number of syllables and the number of groups of adjacent vowel letters (e.g., client ), to other words, controlling for standard lexical variables. In speeded pronunciation, hiatus words were processed more slowly than control words, and the effect was stronger in low-frequency words. In the lexical decision task, the interference effect of hiatus in low-frequency words was balanced by a facilitatory effect in high-frequency words. Taken together, the results support the hypothesis that the configuration of consonant and vowel letters influences the processing of polysyllabic words in English.